2014
DOI: 10.1155/2014/269394
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Protein Model Classification and Retrieval Using Bag-of-Visual-Features

Abstract: In this paper we propose a novel visual method for protein model classification and retrieval. Different from the conventional methods, the key idea of the proposed method is to extract image features of proteins and measure the visual similarity between proteins. Firstly, the multiview images are captured by vertices and planes of a given octahedron surrounding the protein. Secondly, the local features are extracted from each image of the different views by the SURF algorithm and are vector quantized into vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The SURF (speeded-up robust features) descriptor algorithm [51] allows extracting features (~1000) from these images. Thousands of variables are then extracted in each stand to construct a 500-dimensional BoVW vector, containing the most influential features (~500) owing the Bag of Visual World method [27,52,53]. This approach is very popular in agriculture to discriminate between crop and weeds [8,27,51].…”
Section: Image Processingmentioning
confidence: 99%
“…The SURF (speeded-up robust features) descriptor algorithm [51] allows extracting features (~1000) from these images. Thousands of variables are then extracted in each stand to construct a 500-dimensional BoVW vector, containing the most influential features (~500) owing the Bag of Visual World method [27,52,53]. This approach is very popular in agriculture to discriminate between crop and weeds [8,27,51].…”
Section: Image Processingmentioning
confidence: 99%
“…For example, the DALI Z-score [1,8], the Local Feature Profile [9], and the Effective Moment Feature Vector [10], which were generated as three-dimensional maps by dimensionality reduction, have shown that all α-, all β-, α/ β-, and α+β-domains are grouped. Moreover, multi-view rendering of 3D protein structures was used to obtain a 2D image followed by feature extraction [11]. In this method, the codebook is generated by clustering visual words and a histogram is used to explore similarities between protein structures.…”
Section: Introductionmentioning
confidence: 99%